2005
DOI: 10.1074/jbc.m507240200
|View full text |Cite
|
Sign up to set email alerts
|

Human Mitochondrial ClpP Is a Stable Heptamer That Assembles into a Tetradecamer in the Presence of ClpX

Abstract: The functional form of ClpP, the proteolytic component of ATPdependent Clp proteases, is a hollow-cored particle composed of two heptameric rings joined face-to-face forming an aqueous chamber containing the proteolytic active sites. We have found that isolated human mitochondrial ClpP (hClpP) is stable as a heptamer and remains a monodisperse species (s 20,w 7.0 S; M app 169, 200) at concentrations >3 mg/ml. Heptameric hClpP has no proteolytic activity and very low peptidase activity. In the presence of ATP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
121
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 44 publications
9
121
0
4
Order By: Relevance
“…CLPX is a hexameric protein that regulates the activity of CLPP, another serine protease with chaperone activity. 23 The function of Nsp4 or other Nsp proteins is not clear and although it has been suggested that these proteins have a role in vesicular transport and may be associated with lipid rafts, 21,22 our results for Nsp4 suggest it is a mitochondrial protein because it bears a classic mitochondrial import sequence that is removed to generate the mature protein. LRPPR is thought be an RNA binding protein involved in mitochondrial RNA transcript processing.…”
Section: 29mentioning
confidence: 70%
See 1 more Smart Citation
“…CLPX is a hexameric protein that regulates the activity of CLPP, another serine protease with chaperone activity. 23 The function of Nsp4 or other Nsp proteins is not clear and although it has been suggested that these proteins have a role in vesicular transport and may be associated with lipid rafts, 21,22 our results for Nsp4 suggest it is a mitochondrial protein because it bears a classic mitochondrial import sequence that is removed to generate the mature protein. LRPPR is thought be an RNA binding protein involved in mitochondrial RNA transcript processing.…”
Section: 29mentioning
confidence: 70%
“…CLPX, a regulatory component of mitochondrial Clp protease (CLPP), 23 and LRPPR 24 are produced as precursor proteins from which a mitochondrial import sequence is removed. Cleavage is thought to occur after amino acid 64 in CLPX and 59 in LRPPR.…”
Section: Clpx and Lrppr Interact Via N-terminal Ibms Withmentioning
confidence: 99%
“…This observation is also consistent with studies on ClpP proteins from other organisms. Human ClpP, for instance, forms proteolytically inactive heptamers in solution that dimerize upon binding to a chaperone (26). Furthermore, the hetero-oligomeric ClpP of Listeria monocytogenes displays activity only in tetradecameric assemblies as recently published (37).…”
mentioning
confidence: 92%
“…Moreover, it is presently unclear whether the different conformations in the handle domain also impact on the oligomeric state of the protease. Contradicting statements regarding the link between oligomeric organization and activity are found in the literature (22,26). Moreover, the contributions of the residues forming the inter-ring interface have not yet been fully experimentally validated.…”
mentioning
confidence: 99%
“…Interestingly, no homolog of ClpP has been detected in yeast. ClpP functions in a complex with ClpX, a AAA þ chaperone protein in the mitochondrial matrix and it is postulated that ClpX is required for substrate recognition (Kang et al 2002(Kang et al , 2005. The function of ClpXP within mitochondria is not yet clearly defined, however, ClpP is able to degrade a folding impaired mutant of the mitochondrial enzyme, medium chain acyl-CoA dehydrogenase (Hansen et al Proteolytic systems in mitochondria.…”
Section: Atp-dependent Proteolysis In the Mitochondrial Matrixmentioning
confidence: 99%